2015
DOI: 10.1515/cmble-2015-0022
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CEA release from epithelial cells by lipid A of Gram-negative bacteria

Abstract: A number of bacterial species, both pathogenic and non-pathogenic, use the human CEACAM family members as receptors for internalization into epithelial cells. The GPI-linked CEA and CEACAM6 might play a role in the innate immune defense, protecting the colon from microbial invasion. Previous studies showed that CEA is released from epithelial cells by an endogenous GPI-PLD enzyme. GPI-PLD activity was reported to be inhibited by several synthetic and natural forms of lipid A. We hypothesized that CEA engagemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…It has also been suggested that innate responses to pathogen interaction can lead to induction of cytokines that alter expression of CEACAMs by intestinal epithelia, such as the induction of CEACAM5 and CEACAM6 by INF-γ ( 79 ). Conversely, others have argued that Gram-negative organisms might be able to impair release of CEA from intestinal epithelia ( 80 ).…”
Section: Importance Of Ceacam- E Coli Interactionsmentioning
confidence: 99%
“…It has also been suggested that innate responses to pathogen interaction can lead to induction of cytokines that alter expression of CEACAMs by intestinal epithelia, such as the induction of CEACAM5 and CEACAM6 by INF-γ ( 79 ). Conversely, others have argued that Gram-negative organisms might be able to impair release of CEA from intestinal epithelia ( 80 ).…”
Section: Importance Of Ceacam- E Coli Interactionsmentioning
confidence: 99%